(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article experience of acceptance and implementation of the legislation of the United States of America and the European Union concerning ensuring information security of the personality, society and the state is considered. The reasons, the sequence and consequences of adoption of special acts in military and civil spheres are traced. This experience is investigated for a potential possibility of his use for improvement of the information and legal sphere of the Republic of Kazakhstan. Key words: information security, information interests, Internet, mass media and communications.